MENJADI ISLAM SAMA DENGAN MENJADI MISKIN (Studi Adaptasi Muallaf Tionghoa Terhadap Masyarakat Aceh) - Triyanto Triyanto (Prodi Sosiologi FISIP Universitas Teuku Umar, 2016)
Muallaf life of Chinese Crossbreed community in Aceh Barat is not as good as with other crossbreed. Muallaf were expelled from their family, even business relationships between the members of the ethnic Chinese crossbreed also cut off so economically bankrupt and ended up living in poverty. Because of this, part of other ethnic Chinese who wants to convert to Islam with fear and cancel his intention. The emergence of the phrase